TRIBOLOGICAL BEHAVIOR SIMULATION OF HARD DENTAL STRUCTURES USING THE FINITE ELEMENT ANALYSIS - Adina Oana Armencia; Magda Calina Barlean; Loredan Liliana Hurjui; Ancuta Goriuc; Irina Gradinaru; Mihaela Mitrea; Raluca Jipu; Cristina Claudia Tarniceriu; Ion Hurjui; Ramona Feier; Carina Balcos (Romanian Society of Oral Rehabilitation, 2021)
Simulating the biomechanical behavior of a reconstruction using the finite element analysis method is a modern method necessary before the practical stage of a research, thus enabling the precise shaping of certain trajectories in the approach of certain directions of practical applicability, as well as obtaining final results with relevant data (results coupled with experimental models that reiterate the clinical situation that will be later analyzed).